IV Valproate in Refractory Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs, 2000)
The results of treatment of refractory status epilepticus (SE) with IV valproate (VPA) in 41 children are reported from University Hospital for Children, Erlangen, Germany.